Soul food junkies [videorecording (DVD)] - Hurt, Byron, 1970- (God Bless the Child Productions ; distributed by PBS Distribution, 2012)
Filmmaker Byron Hurt looks at the past and future of soul food; from its roots in Western Africa, to its incarnation in the American South, to its contribution to modern health crises in communities of color. Soul Food Junkies also looks at the socioeconomics of the modern American diet, and how the food industry profits from making calories cheap, but healthy options expensive and hard to find.